LCT-13910C > T polymorphism-associated lactose malabsorption and risk for colorectal cancer in Italy - Tarabra, Elena; Pazienza, Paola; Borghesio, Elisabetta; Actis, Giovanni C.; Tappero, Gianfranco; Framarin, Luciana; Ayoubi, Mohammad; Castellino, Francesca; Leone, Nicola; Sansoè, Giovanni; De Paolis, Paolo; Comandone, Alessandro; et al. (Digestive and liver disease, 2010)
The activity of epithelial lactase ( LCT) associates with a polymorphism 13910 bp upstream the LCT-encoding gene ( LCT-13910C > T). The relationship between LCT-13910C > T polymorphism and risk for colorectal cancer is unclear. We examined the relationship between the LCT-13910C > T polymorphism causing lactose intolerance and risk for colorectal cancer/polyps onset in the Italian population. 793 subjects (306 with colorectal cancer, 176 with polyps and 311 controls) were genotyped for the LCT-13910C > T variant by TaqMan real time-PCR. Lactose malabsorption linked to the CC genotype did not associate with an increased risk for either colorectal cancer (OR = 1.041; 95% CI = 0.751–1.442; p = 0.868) or polyps (OR = 0.927; 95% CI = 0.630–1.363; p = 0.769). There was no association with colorectal cancer/polyps site. 60% of the subjects overall bore the CC genotype. In the Italian population the LCT-13910C > T polymorphism is not associated to the risk for colorectal cancer or polyps.